2022
DOI: 10.1007/s40489-022-00344-4
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic and Autism Spectrum Disorder, Consequences to Children and Adolescents — a Systematic Review

Abstract: In this systematic review, we aimed to identify the impact of the COVID-19 pandemic on children/adolescents with a diagnosis of autism spectrum disorder (ASD). The protocol was registered on PROSPERO CRD42021255848. Articles were selected from PubMed, Embase, and LILACS according to these characteristics: patients from zero to 18 years old, exposed to the COVID-19 pandemic, impact on social communication/interaction and restricted/repetitive behavior domains. The Newcastle–Ottawa Scale was used to assess metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 49 publications
0
11
0
4
Order By: Relevance
“…The indicators of frequency and intensity of emotional outbursts worsened or remained the same from Time 1 to Time 2, except for the duration of less severe emotional outbursts, which decreased by 1 point in the maximum score. This result does not compromise the predictive validity of the instrument, and it can be hypothesized that for this reduction in scores, there is evidence from previous studies showing that removing demands, especially social ones such as attending school 35 , was a driver of well-being for autistic pupils and their parents/caregivers 36 .…”
Section: Discussionmentioning
confidence: 84%
“…The indicators of frequency and intensity of emotional outbursts worsened or remained the same from Time 1 to Time 2, except for the duration of less severe emotional outbursts, which decreased by 1 point in the maximum score. This result does not compromise the predictive validity of the instrument, and it can be hypothesized that for this reduction in scores, there is evidence from previous studies showing that removing demands, especially social ones such as attending school 35 , was a driver of well-being for autistic pupils and their parents/caregivers 36 .…”
Section: Discussionmentioning
confidence: 84%
“…In the adolescents with intellectual disabilities all the CBCL scales were significantly higher except for Thought problems and ADHD scales. Several previous studies confirmed a worsening in young people with Autism Spectrum Disorder and Intellectual Disabilities during the COVID-19 pandemic, mainly represented by an increase in anxiety symptoms, irritability hyperactivity and behavioral problems [ 23 , 24 , 25 , 63 ], probably due to changes in their daily routines and access to therapies. Other studies, on the other hand, suggested a reduction in emotional behavioral manifestations in adolescents with autism due to lower social pressure [ 64 ].…”
Section: Discussionmentioning
confidence: 84%
“…In the systematic review by Dal Pai et al [ 23 ] the authors underlined that children and adolescents with Autism Spectrum Disorder (ASD) experienced several pandemic-related issues that impacted their psychological well-being, behavior and sleep patterns. Another study that examined stress and anxiety levels in youth with and without ASD and their parents during the first three months of the pandemic, revealed that ASD families experienced more anxiety and stress [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep was an issue during the pandemic for children and adolescents with ADHD, but also for children and adolescents with autism spectrum disorder, 48 those with epilepsy, 49 and healthy children and adolescents. 46 A meta-analysis found that children and adolescents were the second most prevalent population with sleep problems (42.47%), behind only people with COVID-19.…”
Section: Discussionmentioning
confidence: 99%